Menarche and its Determinants in Adolescent Girls - Ghimire, Moushami; Sharma, Achala; Ghimire, Madhusudhan (Journal of Lumbini Medical College, 2016)
Introduction: Biological, psychosocial, cognitive, emotional and social changes begin during puberty and continue throughout adolescence. The age at which a female reaches sexual maturity is critical in determining her future reproductive health and success. The aim of the study was to assess the average age of sexual feeling and menarche among the adolescent girls and its determinants. Methods: Three hundred fifty five respondents were selected through simple random sampling from three secondary schools (namely Sunrise Boarding School, Swaraswati Secondary School and Gyanjyoti Samudayak Bidhyalaya) in Palpa for the cross-sectional study. Structured interview schedule was used to collect information. Data was tabulated in Microsoft Excel spreadsheet and analyzed with SPSS-16. Results: Most of the girls (44.8%) attained menarche at 12 years (M = 12.4, SD = 1.11). Age at menarche was more likely before 13 years of age when the age of onset of sexual feeling was earlier than 12 years of age, in students than in domestic workers and if they are living with parents than in those not living with parents. Conclusion: The average age of menarche among the adolescent girls was 12.40 years and it could be influenced by age of sexual feeling, occupation and living status of girls. Journal of Lumbini Medical College. 2014;2(1):10-13.